Latent Hypoparathyroidism in Children With Conotruncal Cardiac Defects - Cuneo, Bettina F.; Langman, Craig B.; Ilbawi, Michel N.; Ramakrishnan, V.; Cutilletta, Anthony; Driscoll, Deborah A. (Circulation (New York, N.Y.), 1996)
Background DiGeorge anomaly is characterized by hypoplasia or atresia of the thymus and parathyroid glands resulting in T cell–mediated immune deficiency, hypocalcemic hypoparathyroidism, and conotruncal cardiac defects. It usually is associated with deletions of chromosomal region 22q11. We hypothesized that the stimulated (secretory reserve) but not the constitutive secretion of parathyroid hormone would be reduced in normocalcemic children with conotruncal cardiac defects but no overt immune deficiency and would be related to the presence of a deletion in the DiGeorge chromosomal region of 22q11. Methods and Results Blood-ionized calcium and serum-intact parathyroid hormone were measured at baseline and seven more times during hypocalcemia induced during cardiopulmonary bypass in 22 patients and 10 control subjects with an atrial septal defect. Chromosomal deletions were detected by fluorescent in situ hybridization and DNA dosage analysis. There were no differences in basal calcium and parathyroid hormone levels between patients and control subjects. All had increased parathyroid hormone in response to hypocalcemia; despite lower calcium levels, parathyroid hormone levels were lower in patients. The parathyroid hormone secretory reserve in 14 of 22 patients was reduced compared with control subjects; 4 of the 14 had deletions. Conclusions A significant number of children with conotruncal cardiac defects have normocalcemia and a normal constitutive level of parathyroid hormone but deficient parathyroid hormone secretory reserve; about 30% also have 22q11 deletions. Such children may be at risk for the later development of hypocalcemic hypoparathyroidism.